A Single Pheromone Receptor Gene Conserved across 400 My of Vertebrate Evolution. (24th September 2018) - Suzuki, Hikoyu; Nishida, Hidefumi; Kondo, Hiro; Yoda, Ryota; Iwata, Tetsuo; Nakayama, Kanako; Enomoto, Takayuki; Wu, Jiaqi; Moriya-Ito, Keiko; Miyazaki, Masao; Wakabayashi, Yoshihiro; Kishida, Takushi; et al.
Abstract: Pheromones are crucial for eliciting social and sexual behaviors in diverse animal species. The vomeronasal receptor type-1 ( V1R ) genes, encoding members of a pheromone receptor family, are highly variable in number and repertoire among mammals due to extensive gene gain and loss. Here, we report a novel pheromone receptor gene belonging to the V1R family, named ancient V1R ( ancV1R ), which is shared among most Osteichthyes (bony vertebrates) from the basal lineage of ray-finned fishes to mammals. Phylogenetic and syntenic analyses of ancV1R using 115 vertebrate genomes revealed that it represents an orthologous gene conserved for >400 My of vertebrate evolution. Interestingly, the loss of ancV1R in some tetrapods is coincident with the degeneration of the vomeronasal organ in higher primates, cetaceans, and some reptiles including birds and crocodilians. In addition, ancV1R is expressed in most mature vomeronasal sensory neurons in contrast with canonical V1R s, which are sparsely expressed in a manner that is consistent with the "one neuron–one receptor" rule. Our results imply that a previously undescribed V1R gene inherited from an ancient Silurian ancestor may have played an important functional role in the evolution of vertebrate vomeronasal organ.